Topical Use of Angiopoietin-like Protein 2 RNAi-loaded Lipid Nanoparticles Suppresses Corneal Neovascularization - Taketani, Yukako (Mol Ther Nucleic Acids, 2016)
Corneal neovascularization (CNV) is a sight-threatening condition that is encountered in various inflammatory settings including chemical injury. We recently confirmed that angiopoietin-like protein 2 (ANGPTL2) is a potent angiogenic and proinflammatory factor in the cornea, and we have produced a single-stranded proline-modified short hairpin anti-ANGPTL2 RNA interference molecule that is carried in a lipid nanoparticle (ANGPTL2 Li-pshRNA) for topical application. In this study, we have further examined the topical delivery and anti-ANGPTL2 activity of this molecule and have found that fluorescence-labeled ANGPTL2 Li-pshRNA eye drops can penetrate all layers of the cornea and that ANGPTL2 mRNA expression was dramatically inhibited in both epithelium and stroma at 12 and 24 hours after administration. We also examined the inhibitory effect of ANGPTL2 Li-pshRNA on CNV in a mouse chemical injury model and found that the area of angiogenesis was significantly decreased in corneas treated with ANGPTL2 Li-pshRNA eye drops compared to controls. Together, these findings indicate that this modified RNA interference agent is clinically viable in a topical formulation for use against CNV.